Oral health-related quality of life of children seeking orthodontic treatment based on child oral health impact profile: A cross-sectional study - G Thiruvenkadam; Sharath Asokan; J Baby John; P R Geetha Priya; J Prathiba (Wolters Kluwer Medknow Publications, 2015)
Aims: The aim of this study was to assess oral health-related quality of life (OHRQoL) using short form (SF) of child oral health impact profile (COHIP) in children aged 11-15 years who sought orthodontic treatment. A comparison was done between these children and age-matched peers who never had or sought orthodontic treatment. Methodology: This cross-sectional study included 227 children aged 11-15 years. A total of 110 participants had sought orthodontic treatment at KSR Institute of Dental Science and Research (orthodontic group) and 117 participants from a nearby school who had never undergone or sought orthodontic treatment (comparison group). OHRQoL was assessed with the SF of the COHIP, and malocclusion severity was assessed with the index of orthodontic treatment needs. Data presentation and statistical analysis were performed with the Statistical Package for the Social Sciences Software (Version 19, SPSS, Chicago, IL, USA). The Chi-square test and Fischer exact tests were used to analyze the qualitative data. Results: Children with little to borderline treatment needs have a better quality of life when compared to children with definitive treatment needs (P = 0.049). No statistically significant difference in COHIP-SF scores was found between boys and girls (P > 1.000). In the orthodontic group, children with little to borderline treatment needs were 4.8 times (P = 0.037) more likely to report better OHRQoL when compared to children with definitive treatment needs. Conclusion: Children who sought orthodontic treatment had lower quality of life scores than those who never had or never sought treatment.